2021
DOI: 10.2174/1871520620666201006141317
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Combination of Histone Deacetylase Inhibitor Suberoylanilide Hydroxamic Acid and Natural Flavonoid Curcumin Exhibits Anticancer and Antibacterial Activity

Abstract: Background and Objective: Curcumin is an effective anti-cancer agent used in thyroid cancer treatments. However, its use in clinical applications is limited due to low solubility and bioavailability. In this study, a novel combination strategy was applied by combining curcumin with suberoylanilide hydroxamic acid (SAHA) to increase both bioavailability of curcumin and the efficiency of SAHA, which has limited efficiency when used alone. Methods: MTT assay was used to determine the cell viability of B-CPAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Curcumin was also co-delivered with suberoylanilide hydroxamic acid in order to improve its water solubility and efficacy. The results showed that such a synergistic combination displayed stronger antibacterial action for curcumin than suberoylanilide hydroxamic acid and pure curcumin alone [78].…”
Section: Synergistic Effectsmentioning
confidence: 97%
“…Curcumin was also co-delivered with suberoylanilide hydroxamic acid in order to improve its water solubility and efficacy. The results showed that such a synergistic combination displayed stronger antibacterial action for curcumin than suberoylanilide hydroxamic acid and pure curcumin alone [78].…”
Section: Synergistic Effectsmentioning
confidence: 97%
“…), and pathogenic pathogens (e.g., Staphylococcus aureus , Enteropathogenic Escherichia coli , and Mycobacterium tuberculosis ) [ 54 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Additionally, several clinical studies have shown that curcumin has a strong therapeutic potential for treating a few chronic illnesses, including pulmonary, cancer, neurological, cardiovascular, infectious, neoplastic, psychiatric, and metabolic disorders [ 68 ]. Not surprisingly, several in vitro and animal experimental studies confirmed that curcumin supplementation could offer strong protective effects against AFB1-induced liver injury, mutagenicity, hepatocarcinogenicity, renal dysfunction, ileum damage, immune toxicity via regulating multiple above-mentioned targets [ 26 , 34 , 60 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Biological Properties Of Curcuminmentioning
confidence: 99%
“…Importantly, human trials showed that oral administration of curcumin was safe and effective for skin diseases, including psoriasis, infection, acne, skin inflammation, and skin cancer [14]. Bacterial infections also contribute to tumor formation, and curcumin combinations with some drugs have both anti-cancer and antibacterial activities that would provide a novel thyroid cancer treatment strategy [15]. In the present review, we survey the literature on the antibacterial properties and current underlying molecular mechanism of curcumin per se, curcumin-based combinations, and its nanoformulations, clinical trials, and major challenges, aiming to provide a prospective into the further clinical application of this promising antimicrobial candidate or broad-spectrum antibacterial adjuvant.…”
Section: Introductionmentioning
confidence: 99%